H [infinity] aerospace control design a VSTOL flight application - Hyde, R. A. (Richard Alden) (Advances in industrial control, 1995)
Recent Developments in H¿ theory have produced a promising new design approach. However, a large gap between theory and practice has emerged, with as yet very few design examples applied to real industrial control problems. The work described in this monograph aims to narrow this gap, and to address implementation issues associated with multivariable H¿ controllers. An H¿ control law has been developed and tested for the DRA (Defence Research Agency) Bedford research Harrier. The first part of this text introduces the basic components of the flight control and engine systems and describes the models for the different sub-systems. The second part deals with implementational problems including the discretization process, handling limitations on actuators and the nonlinearities in the system.